2020
DOI: 10.1088/1755-1315/412/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Salt Ponds in Madura Island in 2009-2019 for Managing Sustainable Coastal Environments

Abstract: The salt pond ecosystem has a very important ecological function, especially for the coastal region of Madura. One of the ecological functions of the salt pond is supporting the economy of the community. The purposes of this study are: (1) To determine changes in salt ponds in Madura Island in the last 10 years (2009-2019) based on remote sensing data and Geographic Information System; (2) To make a simulation of structuring the Salt Pond area on Madura Island in the management of a sustainable coastal environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The study's preliminary findings suggest that salt ponds have replaced mangrove land as the primary land use. It is well known that certain studies have revealed a shift in land cover towards salt pond areas in a number of places, particularly on Madura Island or East Java [17,18]. Many coastal areas have a drop in NDVI.…”
Section: Discussionmentioning
confidence: 99%
“…The study's preliminary findings suggest that salt ponds have replaced mangrove land as the primary land use. It is well known that certain studies have revealed a shift in land cover towards salt pond areas in a number of places, particularly on Madura Island or East Java [17,18]. Many coastal areas have a drop in NDVI.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous research, the researchers were intrigued to examine the implementation of various different algorithms to construct a classification system for salt quality. The data used in this study consists of salt data obtained from the Sumenep Regency, which is the largest salt-producing region on Madura Island [12].…”
Section: Introductionmentioning
confidence: 99%